Pattern of drug use among the geriatric patients: a prospective, observational and hospital based study - Jonnalagadda, Ramya; Kumar, Ajay (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The world’s population continues to grow at an unprecedented rate. With the advances in medical therapeutics have contributed to health gains and increase in life expectancy. So strategies to improve prescribing are essential so as to ensure that the medications available to manage concurrent disease states are prescribed appropriately. This study is undertaken to identify patterns of drug use in treating elderly patients and assessment of polypharmacy among the geriatric age group. Methods: The study was approved by institutional ethics committee of Rangaraya Medical College, Kakinada. The study was conducted as a hospital based study in different departments in Government General Hospital during period from January 2016 to December 2016 at Government General Hospital with a total of 549 patients among outpatient and inpatients. Results: Polypharmacy is unfortunately very common in India and some other countries. In the present study average number of drugs prescribed per patient was 4.66. Conclusions: With ever increasing therapeutic options, escalating proportions of older people worldwide, the prescription pattern among them matters a lot. Also as this group of patients are vulnerable, taking necessary care and reviewing the past drug history will have a major role and increase the betterment of the geriatric age group.